PEMAHAMAN ORANG TUA TERHADAP KONSEP DASAR PENDIDIKAN ANAK USIA DINI DI KECAMATAN SENGAH TEMILA - Ratnasari, Wesi; Yuniarni, Desni; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the level of understanding of parents towards the basic concept of ECD in Sengah Temila District. The research method used is quantitative, with the form of survey research, data analysis using descriptive statistics. Data is collected by indirect communication techniques and data collection tools in the form of questionnaires. The sample used was 99 respondents. The results of the study show (1). parents' understanding of the notion of ECD 92% is categorized as